2013
DOI: 10.1007/s11099-013-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation in leaf photosynthetic characteristics in wild rice species

Abstract: Variations in leaf gas-exchange characteristics, leaf pigment content, and other important leaf traits were investigated in seven wild Oryza species, five hybrids and improved varieties. The significant variations were observed in photosynthetic pigment contents amongst different species of Oryza. The mean chlorophyll (Chl) content was higher in O. sativa (varieties and hybrids), while O. eichengeri showed the lowest Chl content. The mean carotenoid (Car) content in O. sativa (varieties and hybrids) was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 11 publications
5
27
1
Order By: Relevance
“…A total of twenty wild rice accessions (Table 1) belonging to six wild spp., two each of Hybrids (DRRH3 and PA 6444) and varieties (AK-Dhan and Varadhan) and a land race (Moroberekan) were grown as described recently from this laboratory (Kiran et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of twenty wild rice accessions (Table 1) belonging to six wild spp., two each of Hybrids (DRRH3 and PA 6444) and varieties (AK-Dhan and Varadhan) and a land race (Moroberekan) were grown as described recently from this laboratory (Kiran et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The current results were in harmony with the reports of Yeo et al (1994) that wild Oryza species had higher photosynthesis than cultivated Oryza sativa. Earlier, Kiran et al (2013) reported using photosynthetic measurements in wild accessions, O. nivara (CR 100097), O. rufipogon (CR 100267), and O. nivara (CR 100008) were superior and useful for breeding purpose (Kiran et al 2013). However, Cook and Evans (1983) reported higher photosynthetic rates in cultivated rice.…”
Section: Respiration and Light Induced Respiration Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Total chlorophyll content (TCC) were measured in 80% acetone following the procedure described by Kiran et al . (2013).…”
Section: Methodsmentioning
confidence: 99%
“…However, the photosynthetic characteristics of 'Chaling' CWR under cold stress remain unknown. There are a few research reports on the photosynthesis of CWR, but these studies were only focused on their photosynthetic characteristics under the optimum temperature condition (Kang et al, 2007;Kiran et al, 2013;Masumoto et al, 2004;Yeo et al, 1994;Zhao et al, 2008;Zhao et al, 2010). Although the cold stress tolerance property of 'Chaling' CWR is well known, its photosynthetic ability under cold stress is little known.…”
Section: Aqy and Ce Measurementsmentioning
confidence: 99%